Political Engagement and Popular Print in Spanish Naples (1503-1707) - Incollingo, Laura (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
What was published in Naples during the Spanish Vicerealm? How did books, pamphlets, broadsheets and newspapers contribute to the political awareness of the Neapolitan people? To what extent did the authorities engage with this politically-charged literary world? This book aims to answer these questions by discussing an untapped body of sources, in manuscript and printed form. What emerges is a vivid picture of a vibrant printing industry and a rich cultural landscape. Three moments of crisis of the seventeenth century - the eruption of Vesuvius, Masaniello's revolt and a major plague epidemic - are used as a test of the capability of the Spanish authorities in regards to political and propagandistic communication. See Less